2023
DOI: 10.1101/2023.10.20.23297203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Recovery Just the Beginning? Persistent Symptoms and Health and Performance Deterioration in Post-COVID-19, non-hospitalised University Students - A Cross-Sectional Study

Ashkan Latifi,
Jaroslav Flegr

Abstract: Many individuals experience persistent symptoms such as deteriorated physical and mental health, increased fatigue, and reduced cognitive performance months after recovering from COVID-19. Current data are limited on the long-term trajectory of these symptoms and their prevalence in milder cases. Our study aimed to assess the persistent effects of COVID-19 on physical and mental health, fatigue, and cognitive performance in a cohort of 214 students, averaging 21.8 years of age. Of these, 148 had contracted COV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
3
1
0
Order By: Relevance
“…Our results also demonstrated that age had a significant and positive association with the course of COVID so the older the patient, the more severe the disease. Again, these results align with previous research findings [ 2 , 38 , 39 ]. It was suggested that older adults may be more vulnerable to the effects of COVID-19 due to their weaker immune systems [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results also demonstrated that age had a significant and positive association with the course of COVID so the older the patient, the more severe the disease. Again, these results align with previous research findings [ 2 , 38 , 39 ]. It was suggested that older adults may be more vulnerable to the effects of COVID-19 due to their weaker immune systems [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…A certain tendency toward improvement was also observed in the reaction times achieved in the Stroop test (Tau = −0.018, P = .192). Our findings, as it regards the persistence of some of the symptoms years beyond the initial COVID-19 infection, are consistent with those from university students [ 2 ], which demonstrated that the effects of COVID on health and performance could persist for several years, even though the participants were young (mean age 21.8) and none required hospitalization during their infection. That study reported that specific effects on mental health, reaction times, and particularly fatigue, may even begin to deteriorate again in the third year after infection, following an initial period of improvement.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations